2017
DOI: 10.1021/acsomega.7b00446
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Site Generated by Natural Changes in Erm Proteins Leads to Unexpectedly High Susceptibility to Chymotrypsin

Abstract: Erms are proteins that methylate the adenine (A2058) in Escherichia coli 23S rRNA, which results in resistance to macrolide, lincosamide, and streptogramin B antibiotics. In a previous report, ErmN appeared to be more susceptible to contaminating proteases in DNase I. To determine the underlying mechanism, cleavage with chymotrypsin over time was investigated. ErmN possesses unusually high-susceptibility recognition site (F45) as evidenced by a band (band 1) that represented greater than 80% of the total band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The expression vector (pHJJ105) and E. coli strain ( E. coli HJJ105) overexpressing ErmS and those (pHJJ202 and E. coli HJJ202) for ErmE were obtained in previous studies ( 15 , 20 ). For constructing an ErmB expression vector, pVA838 plasmid DNA ( 38 ) was used as a DNA template to obtain the mature protein-coding region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression vector (pHJJ105) and E. coli strain ( E. coli HJJ105) overexpressing ErmS and those (pHJJ202 and E. coli HJJ202) for ErmE were obtained in previous studies ( 15 , 20 ). For constructing an ErmB expression vector, pVA838 plasmid DNA ( 38 ) was used as a DNA template to obtain the mature protein-coding region.…”
Section: Methodsmentioning
confidence: 99%
“…Almost 40 different erm methyltransferase genes have been isolated and characterized from diverse sources, ranging from pathogens to antibiotic-producing actinomycetes ( 1 , 2 , 13 , 14 ). Despite the diversity of sources, the significant homology among Erm proteins and their common functional role in methylating the specific adenine residue at position N 6 suggest that they could assume similar structures ( 11 , 15 ) and originate from a common ancestor ( 2 , 16 ). Furthermore, the methylatable adenine (A2058) is located in the peptidyl transferase circle in domain V of 23S rRNA, which has been highly conserved over the course of evolution, presumably because of its functional role as the active site of the ribosome ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both ErmC′ and ErmK could be overexpressed in sufficient quantity to purify and evaluate its methylation activity in vitro . ErmN was successfully expressed in E. coli BL21(DE3) in a previous study ( 20 ), and it could be expressed with and without IPTG induction in soluble form (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…From the Erm family, a total of 44 sequences were aligned, where 41 of them could be retrieved from CARD (comprehensive antibiotic resistance database; [ 22 ]) and ErmI [ 23 , 24 ], Erm50 [ 25 ] and Erm51 [ 26 ] were added to them. To the authors’ knowledge, these are all Erm proteins reported at the time of submission of the paper.…”
Section: Resultsmentioning
confidence: 99%